PRODUKVITAS ALAT ANGKUT UNTUK PEMUATAN NIKEL KE TONGKANG PT GAG NIKEL DISTRIK WAIGEO BARAT KEPULAUAN KABUPATEN RAJA AMPAT PROVINSI PAPUA BARAT - Irene Lestari Sihombing; Jance Murdjani Supit (INTAN Jurnal Penelitian Tambang, 2020)
PT. Gag Nikel sales its product in the form of mix laterite with 1.8% nickel content. The shipping of the product conducted by transportation contractor PT. Sinar Terang Mandiri using nickel shipping barges. There are two barges used, Bisai barge and Seadragon barge. The planed loading capacity of Bisai barge is 13,000 MT in 3 days loading time while Seadragon barge is 8,000 MT in 2 days loading time. Thus, using 89 dump trucks per day, the working time rate of the Bisai barge is 6.95 hours/day while Sedragon barge is 4.92 hours/day. However, the actual loading capacity of Bisai barge is 12,550.27 MT in 4 days loading time while Seadragon barge is 7,528.64 MT in 3 days loading time. In as much, the loading efficiency is less than 100%. This issue most likely due to the utilization of the dump trucks, thus loading time efficiency using the dump trucks should be evaluate to understand the cause and find the solutions.